Knowledge and attitudes of dental students towards treatment of pregnant women: a cross-sectional study - Frey Furtado, Leonor; Melo, Paulo; Azevedo, Álvaro; Listl, Stefan; Pereira, Maria Lurdes (European journal of dental education, 2025)
Introduction The aim of this study is to address the barriers that pregnant women face when accessing oral health care, particularly due to the lack of confidence and knowledge among dental professionals. We focus on final-year Portuguese dental students, aiming to characterise their self-assessed knowledge and attitudes in providing care to pregnant women. Methods and Materials Between March and April 2024, final-year dental students from all Portuguese dental faculties completed a 16-question web-based survey assessing their attitudes and knowledge regarding dental care for pregnant women. Results Among 119 respondents, 98.3% emphasised the importance of dental check-ups during pregnancy, 79.8% were aware of periodontitis' adverse effects, and 75.6% identified the second trimester as optimal for dental visits. However, only 36.1% knew the correct position to prevent hypotension syndrome in the third trimester, and 37.8% were unsure about safe medications. Additionally, 92% supported integrating oral health education for pregnant women into the curriculum, with 95% believing it would increase their comfort in treating pregnant women. Conclusion The study reveals significant deficiencies in the knowledge and attitudes of Portuguese dental students regarding evidence-based dental care for pregnant women. This underscores the urgent need for improved dental education and training to ensure that these students are adequately prepared to provide care to pregnant women.